Anglo-Italian Agreement: points from speech of Lord Halifax, in the House of Lords, 3rd November, 1938 - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
1938-11-03 017b-0037-001 292/946/17b/44(i)